Validation of an 'endovascular-first' approach to spinal dural arteriovenous fistulas: an intention-to-treat analysis. (25th March 2016) - Gross, Bradley A; Albuquerque, Felipe C; Moon, Karam; McDougall, Cameron G
Abstract : Background/objective: Spinal dural arteriovenous fistulas (SDAVFs) require pretreatment angiography; embolization can be performed in the same session. To validate this approach, obliteration and morbidity rates of 'endovascular-first' (embolization and microsurgery in the case of embolization failures) must be compared with rates for 'microsurgery-first' (microsurgical ligation without attempted embolization) approaches. Methods: We reviewed our institutional database (January 1998–October 2015) for SDAVFs, performing an intention-to-treat analysis comparing endovascular-first and microsurgery-first approaches. Results: A total of 71 patients underwent surgical and/or endovascular treatment for SDAVFs. All SDAVFs were ultimately occluded. Of 35 patients under consideration for an endovascular-first approach, radicular artery anatomy or anterior spinal artery embolization risk precluded attempting embolization in seven cases (20%). Among 28 patients undergoing embolization, angiographic non-opacification of the fistula was noted in 18 (64%). Fourteen patients had obliteration with excellent casting of the draining vein (50%) and did not undergo surgery. There were no significant differences in total complications (9% vs 11%; p=1.0) or permanent complications (3% vs 4%; p=1.0) after attempted endovascular and surgical treatment. Based on an intention-to-treat analysis, there were no significant differences in total complications (11% vs 14%; p=1.0), permanent complications (6% vs 3%; p=0.61), or the symptomatic resolution/improvement rate (80% vs 78%; p=1.0) between endovascular-first and microsurgery-first groups. Conclusions: Our results support attempted embolization of SDAVFs prior to consideration of microsurgery, allowing for a less invasive treatment option in the same session as diagnostic angiography.